The wild orchids of Crocker Range National Park, Sabah, Malaysia - Hamelda F. Majit; Lamb, Anthony; Ramlan Miadin; Monica Suleiman (Malaysian Nature Society, 2014)
A checklist of wild orchids of Crocker Range National Park and a short account on common species according to vegetation zone is presented. The checklist is a combined list from numerous fieldtrips throughout the park and living collection from ex situ gardens, as well as from herbarium data and literatures. Currently, 341 species of orchids are reported from the park. Out of this number, 100 are endemic to Borneo and 53 species are endemic to Sabah. The largest genus is Bulbophyllum, followed by Dendrobium and Dendrochilum. The lower montane forest of CRNP has the highest richness of orchids, while the lowland dipterocarp forest has the lowest richness.